Kepemimpinan Kepala Sekolah dalam Meningkatkan Profesionalisme Guru Di SD Islam Terpadu Ulul Albab 01 Purworejo - Siti Saudah (LPPM IAINU Kebumen, 2019)
This research is based on the importance of the principal's leadership in improving teacher professionalism. In this regard, this study aims to determine the leadership of the principal in increasing teacher professionalism at SD IT Ulul Albab 01 Purworejo. This research is a qualitative research. Data collection uses interviews, observation, and documentation, and data validity uses triangulation, and data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. This study resulted in the following conclusions. (1) The principal has Interpersonal Roles in increasing teacher professionalism at the Ulul Albab 01 Islamic Elementary School, Purworejo. This is evident from the school principal who carries out the role of figurehead, leadership, and liaison; (2) The principal has Informational Roles in increasing teacher professionalism at Ulul Albab 01 Islamic Elementary School, Purworejo. This is evident from the school principal who carries out the role of monitor/supervisor, disseminator, and rapporteur; (3) Principals have Decisional Roles in increasing teacher professionalism at the Ulul Albab 01 Islamic Elementary School, Purworejo. This is evident from the school principal who carries out the role of entrepreneur, disturbance-handler, a negotiator role, and a resource allocator.